2013
DOI: 10.21608/jpp.2013.74487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Regimes and Soil Conditioners on Yield, Yield Components and Water Utilization Efficiency of Eg Yptian Clover (Variety Fahl)

Abstract: Two field experiments were carried out at Giza Agriculture Research Station during the two growing seasons of 2010/2011 and 2011/2012. This investigation was aired to study the effect of different levels of irrigation i.e. irrigation at 100, 80 and 60% ETO with the soil conditioner such as compost and humic acid on Egyptian clover variety (Fahl) yield, yield components and crop-water relations. The experimental treatments were arranged in a split plot design with three replicates. The main plots represented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Foliar spray of 10 ml/L K-humate increased N, P and K% more than control by 13.73, 41.38 and 36.36%, respectively. In this respect, Abbas et al (2013) found that application of humic acid on Fahl clover plant exhibited the highest values of N, P and K%. Such finding may be attributed to the favorite effect of humic acid in enhancing mineral nutrients uptake by plants, through its effect on the permeability of roots membranes (Mesut et al, 2010).…”
Section: B-crude Fiber %mentioning
confidence: 89%
See 1 more Smart Citation
“…Foliar spray of 10 ml/L K-humate increased N, P and K% more than control by 13.73, 41.38 and 36.36%, respectively. In this respect, Abbas et al (2013) found that application of humic acid on Fahl clover plant exhibited the highest values of N, P and K%. Such finding may be attributed to the favorite effect of humic acid in enhancing mineral nutrients uptake by plants, through its effect on the permeability of roots membranes (Mesut et al, 2010).…”
Section: B-crude Fiber %mentioning
confidence: 89%
“…In this connection, Sadek and Sallam (2012) found that foliar spray with humic acid on barley plant resulted in substantial promotion of the studied growth parameters, kernel weight/spike and 1000 grains weight compared to control. Abbas et al (2013) stated that treated mono-cut Egyptian clover (Fahl) plants with humic acid increased growth, yield and yield components traits compared with control. Moraditochaee et al, (2012) on cowpea plant found that foliar spray with amino acid increased number of pods/plant and seed yield.…”
Section: Ii-yield and Yield Componentsmentioning
confidence: 99%
“…The superiority effect of HA obtained herein may be due to its role in enhancing the uptake of macronutrients such as N, P and S (Chen and Aviad, 1990) or micronutrients such as Fe, Zn, Cu, Mn (Chen et al, 1999).Moreover, the superiority effect of SA may be due to its role in ion uptake and transport (Khan et al, 2003), the regulation of plant growth and development (Horvath et al, 2007) and enhancement of plant resistance against different biotic and abiotic stress through different mechanism (Kadioglu et al, 2011). In this concern, many investigators found improving effects of some tested stimulant substances such as HA on plant height of clover (El-Hefny, 2010; Daur, 2014 and El-Maaz and Ismail, 2016), leaf area of cowpea (El-Hefny, 2010) and peas (Osman and Rady, 2012) and total dry weight of clover (Abbas et al, 2013) and cowpea (El-Hefny, 2010) as well as AS on number of stems / clover plant (Kumar et al, 2013 andRani et al, 2017).…”
Section: Tablementioning
confidence: 99%